Perception of Medical Students on the Effect of Covid-19 on Medical Education in Nigeria - Adeleke Victor Fasiku; Ibrahim Abdulsamad; James Kolade Adegoke; Adedeji Samson Afolabi; Samson Olaniyi Adedayo; Ayomide Olanipekun; Temitope Olumuyiwa Ojo (University Library System, University of Pittsburgh, 2021)
Background: The lockdown due to the COVID-19 pandemic disrupted normal activities including undergraduate medical education in Nigeria, similar to the rest of the world. Nigeria as a low- and middle-income country had peculiar challenges in adjusting to the new norm. This study aimed to assess Nigerian medical student's perception of the effect of COVID-19 on their learning. Methods: A semi-structured, pre-tested online questionnaire was administered to consenting medical students from thirty-three medical schools in Nigeria. Questions assessed the effect of COVID-19 on study and wellbeing, as well as the perception of interventions from institutions and student organizations to reduce the lockdown consequence on learning. Data was analyzed using (SPSS) version 25. Results: A total of 623 students from 33 institutions participated. All private institutions and 25% of public institutions had commenced online lectures/tutorials, 92% of students in private institutions and 21% in public institutions had attended online lectures/tutorials. Of those who did not attend institution-organized classes, 30.5% were opposed to online lectures, the main reasons stated being internet cost/availability and inefficiency. About 65% of the participants were aware of student-organized online tutorials/seminars. Eighty percent did not feel motivated to study and perceived their personal study to be less effective. Conclusion: Nigerian medical student's perception of the effect of COVID-19 on their medical education was largely negative. Private institutions fared better in coping with the challenges of the pandemic. Proper planning will be needed to curb the effect of COVID-19 on students' health and wellbeing.